Serangga yang Berpotensi sebagai Hama pada Tanaman Duku (Lansium domesticum Corr) di Wilayah Desa Kepur Kabupaten Muara Enim - Umayya, Larasati Nur; Irsan, Chandra; Mulawarman, Mulawarman; Shobiha, Salma Naswa; Fani, Gio; Apriyani, Mella; Aulia, Hamidah; Mirsya, Sabryna Aulia (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Umayya, L.N., Irsan, C., Mulawarman, M., Shobiha, S.N., Fani, G., Apriyani, M., Aulia, H., Mirsya, S.A. (2024). Insects found on duku plants (Lansium domesticum Corr) in Muara Enim Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembangg 21 Oktober 2024. (pp. 212–220). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Cultivation of duku plants has obstacles such as applying of low cultivation technology and interference from Plant Disease Organisms (OPT). Therefore, we need to know the identification of pests that attack duku plants in the area to determine what pest species are causing damage to duku plants. The method used is direct observation and interviews. The results of observations carried out in farmers' duku gardens in Kepur Village, Muara Enim Regency show that insects that have the potential to become pests consist of 6 species, such as red caterpillars, fruit flies, ladybugs, tree termites, plutellidae larvae, and dompolan lice, in contrast other pests attack duku plants are bats and ants. Red caterpillars attack the skin on duku stems, termites attack the lower stems, dompolan lice attack the fluid on the leaves, ladybugs attack young fruit and fruit flies attack the inside of the fruit. Production can be reduced by up to 50-100 kg/stem due to pest attacks on duku plants. Dompolan lice attack duku plants which have a symbiotic relationship with ants. From this description, it was found that tree termite pests are the pests with the highest population and most insects attack the stems of plants. To develop duku production, further research is needed to control pests on duku plants.